Hirsutism. Issue 3 (March 2014) - Sornalingam, Sangeetha; Cooper, Max
Hirsutism is thought to affect 1 in 10 premenopausal women. The most common cause remains polycystic ovarian syndrome, however, other rare but serious diagnoses must be excluded. Regardless of the cause, hirsutism can have a significant effect on self-esteem and quality of life for those affected and GPs need to know how this condition can be managed.